Impact of Di-(2-Ethylhexyl)-Phthalate on Metabolic Syndrome: Insights from Network Toxicology and Molecular Docking and Dynamics - Chen L; Huang YL; Liu F; Huang N; Zeng DC; Zhong YB; Liao JH; Wang MY (Diabetes, Metabolic Syndrome and Obesity)
Long Chen,1,2 Yu-li Huang,1,2 Fang Liu,1,2 Nan Huang,1,2 Ding-cheng Zeng,3 Yan-biao Zhong,2 Jing-hai Liao,2 Mao-yuan Wang2,4,5 1School of Rehabilitation, Gannan Medical University, Ganzhou, Jiangxi, People’s Republic of China; 2Department of Rehabilitation Medicine, First Affiliated Hospital of Gannan Medical University, Ganzhou, Jiangxi, People’s Republic of China; 3The First Clinical Medical School, Gannan Medical University, Ganzhou, Jiangxi, People’s Republic of China; 4Ganzhou Intelligent Rehabilitation Technology Innovation Center, First Affiliated Hospital of Gannan Medical University, Ganzhou, Jiangxi, People’s Republic of China; 5Ganzhou Key Laboratory of Rehabilitation Medicine, First Affiliated Hospital of Gannan Medical University, Ganzhou, Jiangxi, People’s Republic of ChinaCorrespondence: Mao-yuan Wang, Department of Rehabilitation Medicine, First Affiliated Hospital of Gannan Medical University, 128 Jinling Road, Zhanggong District, Ganzhou, Jiangxi, 341000, People’s Republic of China, Email wmy.gmu.kf@gmail.com Jing-hai Liao, Department of Rehabilitation Medicine, First Affiliated Hospital of Gannan Medical University, 128 Jinling Road, Zhanggong District, Ganzhou, Jiangxi, 341000, People’s Republic of China, Email 823851960@qq.comBackground: Metabolic syndrome (MetS) is strongly associated with exposure to environmental pollutants, especially endocrine disruptors (EDCs). Di-(2-ethylhexyl)-Phthalate (DEHP), a typical EDC widely found in plastic products, has been shown to interfere with lipid metabolism and insulin signalling. However, the specific molecular mechanism by which it mediates MetS remains unclear.Purpose: This study aimed to systematically investigate the molecular mechanisms underlying the effects of the ubiquitous environmental pollutant DEHP on MetS, thereby providing new insights into the role of environmental toxins in metabolic disorders.Methods: MetS-related disease targets were searched using the GeneCards, OMIM, and TTD databases. DEHP-related targets were obtained from STITCH, SwissTargetPrediction, and ChEMBL. Constructed PPI networks of intersecting targets and visualized and screened core targets in Cytoscape 3.7.1. GO and KEGG pathway analyses were performed using the DAVID database to elucidate biological processes, cellular components, molecular functions, and key pathways (p< 0.05). In addition, molecular docking and molecular dynamics simulations were used to analyze the interactions between compounds and targets further.Results: 150 intersecting targets were identified between DEHP and MetS. The PPI network exhibited core targets, including TP53, ESR1, EGFR, TNF, and IL6. GO analysis showed entries in metabolic processes, transcriptional regulation, and redox reactions. The KEGG pathway showed significant enrichment in AGE-RAGE, FoxO, insulin resistance, and steroid hormone biosynthesis pathways. DEHP showed strong binding affinity to core targets: TP53 (− 5.6 kcal/mol), ESR1 (− 6.1 kcal/mol), EGFR (− 5.4 kcal/mol), and IL6 (− 4.8 kcal/mol). Molecular dynamics simulation further verified the results of molecular docking.Conclusion: Our study highlights the interaction between environmental pollutants and metabolic dysfunction. These findings highlight the potential role of DEHP in exacerbating MetS and provide a basis for mitigating its health risks through targeted interventions. Further experimental validation is needed in the future to confirm these mechanistic insights.Keywords: DEHP, metabolic syndrome, network toxicology, molecular docking